Perancangan Sistem Informasi Manajemen Kost Berbasis Website Pada Kost Bima Dengan Metode Prototype - Zendrato, Mei Albert; Heksaputra, Dadang; Harahap, Avrillaila Akbar; Wicaksono, Yanuar (Informatik : Jurnal Ilmu Komputer, 2025)
Advances in information technology have encouraged various sectors, including boarding house management, to utilize digital systems. Kost Bima in Tamantirto Village, Bantul, faces challenges in recording tenants, verifying payments, and handling complaints, which are still done manually, thus being time-consuming and prone to irregularities. This study aims to design a website-based boarding house management information system as a solution. The system is designed for three users: admin (boarding house owner), tenants, and prospective tenants. The prototype method was used so that development involved user input at every stage, and in the process, two iterations were carried out to refine the system. The result is a system with features for room reservations, lease extensions, payments, complaint management, and tenant data. Black-box testing showed that all features worked well without bugs. In addition, User Acceptance Testing (UAT) was conducted with five assessment aspects: Learnability, Efficiency, Memorability, Errors, and Satisfaction. The UAT results showed an excellent score of 87.8%, indicating that the system is feasible for use.